Making the Financial Case for Learning - Novak, Clare; American Society for Training and Development (Infoline, 2012)
"As performance improvement professionals, we clearly see the alignment between our initiatives and company goals, and we're passionate about it. But to get buy-in from decision makers, we need to communicate this connection in a language they understand — the language of finance. This Infoline will help you understand basic financial concepts and terms so that you can gain credibility in the eyes of stakeholders and prove the value of your training programs"
Keywords: Employees : Training of; Business enterprises : Finance